On DMT methods to calculate adhesion in rough contacts. (February 2019) - Violano, G.; Afferrante, L.
Abstract: In this paper, we compare different rough contact-mechanics theories with the assumption of weak interfacial adhesion. Two different approaches for the local modeling of adhesion are also considered: the DMT force approach (DMT-F) and the Maugis' approximation (DMT-M). The first approach is based on the idea of summing up attractive interactions that act outside the contact zone; the latter considers a constant adhesive load for each asperity in contact. A comparison with numerical data proves the DMT-F approach is very accurate when hard solids and low adhesive interactions are considered. The DMT-M approach shows, instead, less accuracy especially at low fractal dimensions. Highlights: An advanced multiasperity model has been extended to account for adhesion of randomly rough surfaces. Adhesion is introduced according to the DMT force approach (DMT-F) and Maugis approximation (DMT-M). Comparison with numerical models shows the accuracy of the proposed model combined with the DMT-F approach. The DMT-M approach turns out to be much less accurate especially at low fractal dimensions.